Biblioteka miejscem nauki i spotkań = The Library as a Place for Learning and Meetings - Spodzieja, Irena (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The Public Library in Babimost has the opportunity to celebrate its 75th anniversary in a new, functional location. In 2024, funding was secured for this purpose from the National Reading Development Program 2.0, Priority 2 "Library Infrastructure 2021-2025," in the amount of PLN 2,250,000. The project currently underway involves the renovation and repurposing of the former cultural centre building into a public library. The article outlines the history of the Wiesław Sauter Public Library in Babimost and the project?s design goals. The new location is expected to open in the first half of 2025.
Keywords: adaptacja; przebudowa; Babimost; infrastruktura bibliotek; adaptation; renovation; library infrastructure